2007
DOI: 10.1080/17449200701520099
|View full text |Cite
|
Sign up to set email alerts
|

Women, the embodiment of health and carceral space

Abstract: Using the example of women incarcerated in Canada, this paper aims at showing the necessity of studying prisoners' health and healthcare through a perspective informed both by a criminology of the body and prison/penal sociology. Health is too often constructed as a set of discrete variables that can be isolated from the whole person and her environment. In this paper, we want to show the complexities and richness of situating carceral health and healthcare within the experience of the body and prison. After d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 28 publications
2
37
1
1
Order By: Relevance
“…The reported health complaints were frequent, which corroborates the findings of Butler et al [5] and Robert et al [27], indicating that health complaints among female inmates are frequent during imprisonment. This might be a result not only of their vulnerability in terms of mental and physical health, but also of the increase in self-awareness due to their imprisonment [27].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The reported health complaints were frequent, which corroborates the findings of Butler et al [5] and Robert et al [27], indicating that health complaints among female inmates are frequent during imprisonment. This might be a result not only of their vulnerability in terms of mental and physical health, but also of the increase in self-awareness due to their imprisonment [27].…”
Section: Discussionsupporting
confidence: 81%
“…Regarding health surveillance before imprisonment, most inmates reported they had seen their GP and/or a health professional in emergency services at least once during the 6 months prior to imprisonment, suggesting that access to community health services is frequent, contrary to what other studies have documented [16, 21, 26, 27]. However, the reason for this behavior is not included in this study.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Furthermore, it is confirmed that prisoners report a deterioration of their health status during their detention [3,30,[60][61][62]. The age constitutes an important factor.…”
Section: Discussionmentioning
confidence: 69%